Managers' performance evaluation using a four-axis model: a case study of an Iranian industrial company. (1st October 2019) - Hamidi, Ali
Performance evaluation is of a great importance in human resource management. Compared with other approaches, it is so influential that we can resemble it to the heart of HRM. Since managers play the most important role in adopting and applying organisation strategies, evaluating their performance needs to be done in a comprehensive way. In this paper, a comprehensive practical model is proposed to evaluate the performance of managers. Competency, behaviour, short run and long-term output indexes are four factors considered in the model. To validate, the model has been deployed in an industrial company. In the end, conclusion and future work suggestions are presented. The great finding of this model is the significant focus of the managers on the results of the process that led to a good growth in performance of the managers and staff of the industrial company.